2023
DOI: 10.1002/eom2.12428
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐thermo‐electric hydrogel with interlocking photothermal layer and hydrogel for enhancement of thermopower generation

Jingjie Shen,
Chenhui Yang,
Yanli Ma
et al.

Abstract: Photothermal devices and thermoelectric cells hold great promise for energy generation but integration of the two remains a considerable challenge in real‐life power supply for sensors. Here, a novel photo‐thermo‐electric hydrogel (PTEH‐Interlocking) was constructed by the synthesis of a photothermal layer on a thermoelectric hydrogel with the redox pair Fe(CN)63−/Fe(CN)64−. The smart design of using the oxidation of pyrogallic acid by Fe(CN)63− to construct the photothermal layer for photo‐to‐heat conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…However, although a large number of research results have successfully confirmed the existence of hydroelectricity, the current and power densities embodied in them are far from meeting the needs of commercial applications . Therefore, in order to realize the early and large-scale application of this technology, hydroelectric power generators urgently need to be integrated and applied to provide a clean, convenient, and safe way of energy production for human life …”
Section: Introductionmentioning
confidence: 99%
“…However, although a large number of research results have successfully confirmed the existence of hydroelectricity, the current and power densities embodied in them are far from meeting the needs of commercial applications . Therefore, in order to realize the early and large-scale application of this technology, hydroelectric power generators urgently need to be integrated and applied to provide a clean, convenient, and safe way of energy production for human life …”
Section: Introductionmentioning
confidence: 99%